NUTRISI PADA PENDERITA SAKIT KRITIS - Wiryana, Made (journal of internal medicine; Vol. 8, No. 2 Mei 2007)
Malnutrition is always been being associated with the increase of morbidity and mortality rate due to lack of immune system, depending on ventilator, high rate of infection, and delayed healing process, so it will increase the cost and length of stay of the patients. Clinician need to have right information about how to manage nutrition for critical ill patient because it will influence the outcome of ICU patient. Objective measurement nutritional status of the patient is difficult because process of illnesses itself will disturb the method that will be used in the population. Nutritional status is multidimension phenomenon that need several methods for measurement, including associated factors of nutrition, nutrition intake, and energy expenditure. Nitrogen balance can be used to determine effectiveness of nutritional therapy. Nitrogen balance can be counted by formula that count nitrogen in 24 hours from patch urine, especially urine urea nitrogen (UUN), minus nitrogen intake from the food. Resting Energy Expenditure (REE) must be determined for nutritional therapy in critical ill patients. Acuracy estimation REE will help to reduce complications due to overfeeding, such as infiltration fat to liver and pulmonyary compromise. Several methods are available to predict REE such as Calorimetry, and Harris-Benedict equation. The goal in nutritional therapy in critical ill patient is to support metabolic, not to complete their need in that time. Because in critical ill patient there is no metabolic condition is able to metabolize total amount of calories to fulfill lack of energy expenses. Ideally the route of nutritional therapy is able to supply nutrition with minimal morbidity. Each routes (parenteral and enteral) have advantages and disadvantages, and the choice is depend on patient condition. In critical ill patient care, enteral nutrition is always being the first choice and parenteral nutrition become the next alternative.
Keywords: nutrition therapy, critically ill patients, intensive care uni